Faith, Reason, and Worldviews - Buijs, Joseph A. (Sophia, 2013)
This critical review of Responses to the Enlightenment focuses on the relationship between faith and reason as advanced by Hendrick Hart and William Sweet, respectively. It does so in the context of Enlightenment critique of faith, from which both Hart and Sweet seek to salvage religious faith. While faith as trust is admitted to be performative (Hart), faith is also belief with cognitive content (Sweet). However, faith and reason, as I contend, stand in a dialectical relationship between the need for commitment and understanding at the root of religious as well as secular traditions or worldviews.